2022
DOI: 10.1038/s41467-022-30130-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive molecular features of regenerative stem cells in the damaged male germline

Abstract: Maintenance of male fertility requires spermatogonial stem cells (SSCs) that self-renew and generate differentiating germ cells for production of spermatozoa. Germline cells are sensitive to genotoxic drugs and patients receiving chemotherapy can become infertile. SSCs surviving treatment mediate germline recovery but pathways driving SSC regenerative responses remain poorly understood. Using models of chemotherapy-induced germline damage and recovery, here we identify unique molecular features of regenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
(175 reference statements)
0
15
0
Order By: Relevance
“…To validate the hypothesis, we performed further in vitro validation experiment to confirm the synergistic effects of the combination of anti-HER2 and the PI3K-AKT inhibitors. As reported in the previous studies, buparlisib (BKM120) is a commonly used potent, pan-class I PI3K inhibitor approved for clinical trials [48][49][50] . We treated NCI-N87 cells (HER2-positive cell line) with trastuzumab (TRA), buparlisib (BUP), and combination of trastuzumab and buparlisib (BUP + TRA) with a ratio of 1:1, respectively.…”
Section: T Cell Receptor Signaling Pathway Exerts Diverse Effects In ...mentioning
confidence: 88%
“…To validate the hypothesis, we performed further in vitro validation experiment to confirm the synergistic effects of the combination of anti-HER2 and the PI3K-AKT inhibitors. As reported in the previous studies, buparlisib (BKM120) is a commonly used potent, pan-class I PI3K inhibitor approved for clinical trials [48][49][50] . We treated NCI-N87 cells (HER2-positive cell line) with trastuzumab (TRA), buparlisib (BUP), and combination of trastuzumab and buparlisib (BUP + TRA) with a ratio of 1:1, respectively.…”
Section: T Cell Receptor Signaling Pathway Exerts Diverse Effects In ...mentioning
confidence: 88%
“…For example, in a mouse model, mTORC1 and FOXO1 signaling have been shown to be key regulators for regenerative undifferentiated spermatogonia. 361 The hepatic stellate cell activation pathway is upregulated in SSCs, suggesting its role in the specification and maintenance of SSC fate. 343 The SSC niche is another regulatory layer for SSC development.…”
Section: Adult Germline Stem Cellsmentioning
confidence: 99%
“…Some parts of the figure were drawn by Figdraw SSC transplantation for fertility preservation in cancers and gene therapies. Spermatogonial stem cell transplantation is a promising approach to restore fertility for patients who need chemotherapy and radiation treatment, such as in cancer therapies, because these treatments often lead to damage to gonadal cells, thus infertility, 361,378,379 although some antioxidants can reduce the damage to germ cells. 380 Prepubertal boys who suffer from gonadotoxic treatment under pediatric cancer circumstances, e.g., acute lymphoblastic leukemia and testicular cancer, might cause sterile for the rest of their life.…”
Section: Adult Germline Stem Cells Spermatogonial Stem Cells For Sper...mentioning
confidence: 99%
“…S11). Moreover, a previous study has shown that six of the seven genes are significantly up-regulated in spermatogonial stem cells during regeneration as compared to a homeostatic state ( 68 ). Our analyses further reveal that these seven genes also share common regulatory motifs at their promoter regions in mice and humans (Fig.…”
Section: Resultsmentioning
confidence: 96%